Optimization of arterial spin labeling MRI for quantitative tumor perfusion in a mouse xenograft model†. (24th June 2015) - Rajendran, Reshmi; Liang, Jieming; Tang, Mei Yee Annie; Henry, Brian; Chuang, Kai‐Hsiang
<x xml:space="preserve">Abstract</x> Perfusion is an important biomarker of tissue function and has been associated with tumor pathophysiology such as angiogenesis and hypoxia. Arterial spin labeling (ASL) MRI allows noninvasive and quantitative imaging of perfusion; however, the application in mouse xenograft tumor models has been challenging due to the low sensitivity and high perfusion heterogeneity. In this study, flow‐sensitive alternating inversion recovery (FAIR) ASL was optimized for a mouse xenograft tumor. To assess the sensitivity and reliability for measuring low perfusion, the lumbar muscle was used as a reference region. By optimizing the number of averages and inversion times, muscle perfusion as low as 32.4 ± 4.8 (mean ± standard deviation) ml/100 g/min could be measured in 20 min at 7 T with a quantification error of 14.4 ± 9.1%. Applying the optimized protocol, heterogeneous perfusion ranging from 49.5 to 211.2 ml/100 g/min in a renal carcinoma was observed. To understand the relationship with tumor pathology, global and regional tumor perfusion was compared with histological staining of blood vessels (CD34), hypoxia (CAIX) and apoptosis (TUNEL). No correlation was observed when the global tumor perfusion was compared with these pathological parameters. Regional analysis shows that areas of high perfusion had low microvessel density, which was due to larger vessel area compared with areas of low perfusion. Nonetheless, these were not correlated with hypoxia or apoptosis. The results suggest that tumor perfusion may reflect certain aspect of angiogenesis, but its relationship with other pathologies needs further investigation. Copyright © 2015 John Wiley & Sons, Ltd.